Challenges of denosumab in giant cell tumor of bone, and other giant cell-rich tumors of bone. Issue 4 (July 2019) - Lipplaa, Astrid; Dijkstra, Sander; Gelderblom, Hans
Abstract : Purpose of review: Giant cell tumor of bone (GCTB) is an uncommon benign primary bone tumor, consisting of receptor activator of nuclear factor kappa-B (RANK) expressing reactive osteoclast-like giant cells and neoplastic spindle-shaped cells. Denosumab was approved by FDA in 2013 and by EMA in 2014 to treat adults and skeletally mature adolescents with unresectable GCTB or when resection is likely to result in severe morbidity. However, there is much discussion regarding the optimal applied treatment strategy. Recent findings: Neoadjuvant treatment of GCTB with denosumab can effectively downstage tumors to facilitate less morbid surgery or completely avoid the need for resection, but there is concern about local recurrence postsurgery. Definitive treatment of unresectable GTCB improves symptoms and halts tumor progression. The optimal treatment duration is unclear and long-term treatment is associated with adverse events like osteonecrosis of the jaw (ONJ) and atypical femoral fractures. Denosumab maintenance dose interval is currently being investigated. Summary: For the related but heterogenous group of giant cell rich tumors of bone, like aneurysmal bone cysts (ABC) and central giant cell granuloma (CGCG), denosumab is a new treatment modality under investigation. Given the effectiveness in GCTB, this could be a promising treatment option for selected patients with advanced disease.